The Influence of Knowledge, Attitude, and Practice on Earthquake Disaster Preparedness among Residents of Rusunawa KS Tubun, Jakarta - Mutiara Hildadien Ningharyana; Fatmah Fatmah; Avianto Amri (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2026)
DKI Jakarta faces a high risk of earthquake disasters due to the existence of the Baribis Fault, particularly for residents of vertical housing such as Rusunawa KS Tubun. This study aims to analyze the influence of knowledge, attitude, and practice on earthquake disaster preparedness among residents of low-cost apartments. The conceptual framework of this study is based on the Knowledge, Attitude, and Practice (KAP) Theory to explain how knowledge influences attitude, which then shapes actual practice as an indicator of preparedness. The research method employs a quantitative approach by distributing questionnaires to 240 respondents who are residents of Rusunawa KS Tubun. Data were analyzed using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method via SmartPLS 3 software. The results indicate that knowledge has a significant influence on attitude, practice, and disaster preparedness. A crucial finding in this study is that attitude was found to have no significant influence on practice within the context of earthquake preparedness at the research site. Variables of knowledge, attitude, and practice simultaneously exert a moderate influence on disaster preparedness, with an R2 value of 0.490. The conclusion of this study emphasizes that directly increasing knowledge is more effective in shaping the practice and preparedness of residents compared to attitude-based interventions alone. These findings are expected to serve as a reference for apartment managers and relevant agencies in designing more effective disaster preparedness programs for low-income communities in vertical housing.